Investigação do efeito da nucleação, da velocidade de crescimento e da distribuição da energia armazenada na recristalização pelo método do autômato celular em três dimensões - Assis, Weslley Luiz da Silva (2008)
The recrystallization kinetics has frequently been analyzed with aid of the theory of Johnson, Mehl, Avrami and Kolmogorov (theory JAMK). The analytic model of JMAK uses some suppositions for the description of the recrystallization phenomenon, such as: constant and uniform velocity of progresses of the interfaces, random distribution of the nuclei inside of the matrix and nuclei with spherical shapes. In practice those considerations not always they are true. Aware of this Vandermeer and Rath developed a methodology to study the recrystallization kinetics, in reactions with interfaces with varied speed. Though, the analytic model of Vandermeer and Rath still used the supposition that the velocity was uniform, the nuclei were distributed randomly inside of the matrix and with spherical shapes. In this work they were appraised situations considered by the theories of JMAK and Vandermeer. Other situations in which the analytic theories are scarce were also studied such as: I study from the effect to the random, and of the heterogeneity of energy stored at the matrix. Besides the two studies mentioned above they were also made studies of the geometric aspect and of the evolutionary behavior of individual grains, and of the effect of the rate of nucleation of the constant nucleation. All the studies were accomplished starting from results of the computational simulations, being used the cellular automata's method and experimental results obtained in the literature. The cellular automata's code was developed to simulate the recrystallization, however it can be adapted for any nucleation reaction and growth.